KAJIAN SIMULASI KELAYAKAN SISTEM PEMISAHAN SAMPAH RUMAH TANGGA PADA PENGELOLAAN SAMPAH DI KOTA PEKANBARU (SUATU SIMULASI KEBIJKAN) - Tengku Abu Hanifah (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2006)
The scenario simulation of old and new solid waste management systems in Pekanbaru with constructed model were done. The objective of the simulation was to know the feasibility of the solid waste management system financially. the scenario was simulated from 1999 to 2008.